Prácticas de manipulación del propofol: resultados de un estudio colombiano de corte transversal. - Zorrilla-Vaca, Andrés; León, Tatiana; Ariza, Fredy (Colombian Journal of Anesthesiology / Revista Colombiana de Anestesiología, 2017)
Introduction: Propofol is one of the most frequently used intravenous anesthetic agents. Due to its lipid-based composition, propofol requires a strict handling protocol to avoid increased risk of extrinsic contamination. Little is known about propofol handling practices in developing countries. Objective: We conducted a survey among the population of anesthesiologists and anesthesia residents in Colombia, with a view to identify the practices and factors associated with inadequate propofol handling. Methods: Cross-sectional study based on digital and/or telephone surveys addressed to anesthesiologists and residents of anesthesia in Colombia. The data collection tool comprised thirty questions divided into sections considering socio-demographic conditions, practices and knowledge. Results: A total of 662 answers were analyzed. The reuse of propofol vials in more than one patient and the reuse of propofol syringes in several patients were described as usual practices by 37,9% (251/662) and 6,2% (41/662) respectively, among the subjects surveyed. Multivariate analysis showed a perception of shortage of propofol, infrequent use of gloves, and reuse of syringes that were significantly associated with the reuse of propofol vials at institutions with few ORs (< 9). Conclusions: Notwithstanding the economic conditions, the reuse of propofol in Colombia is similar to developed countries. Further research focusing on the impact of external factors such as economic, administrative, and training conditions is required.